The Business Viability of PT Garuda Indonesia - Haris, Haris; Olfebri, Olfebri; Andri, Andri (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2014)
Through the ability of technology, facilities, infrastructures, and sufficient operational activities, business competition in air transport service is becoming tighter. All airlines are competing to be the best. As one of the most experienced companies, in fact, PT Garuda Indonesia has experienced hard times. By using qualitative and quantitative methods with Altman Z Score method, it is found that in the period of 2003-2007 PT Garuda Indonesia faced a very critical situation. Only in 2007, this company started to recover and improve.